Pengembangan Modul Ajar Berbasis Case Method terhadap Kemampuan Pemecahan Masalah dalam Materi Relasi dan Fungsi pada Siswa SMP - Riska, Maria; Darma, Yudi; Nurmaningsih, Nurmaningsih (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop a Case Method-based Teaching Module to improve problem-solving skills in the subject of Relations and Functions of junior high school students. The research method used is Research and Development (R&D) with a 4-D development model. The subjects of the study were eighth-grade students in one of the junior high schools. Data were collected through problem-solving ability tests, validation sheets, and student and teacher response questionnaires. The data analysis techniques used were validity, practicality, and effectiveness. The results of the study indicate that the Case Method-based Teaching Module developed meets the criteria of validity, practicality, and effectiveness. Based on the description of the research results that have been described, a learning tool in the form of a Case Method-based Teaching Module was obtained to improve students' problem-solving skills using a 4-D development model with the stages of define, design, develop, and disseminate. Thus, the Case Method-based Teaching Module on the subject of Relations and Functions can be an effective alternative to improve students' problem-solving skills.